2022
DOI: 10.1021/acsami.1c20643
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surface Layer Formation during Cycling on the Thermal Stability of the LiNi0.8Co0.1Mn0.1O2 Cathode

Abstract: In this study, the effects of charge/discharge cycling on the thermal stability of LiNi 0.8 Co 0.1 Mn 0.1 O 2 , a high-Ni cathode material, are systematically investigated. X-ray diffraction measurements show that there is almost no change in the bulk structure of the cathode after cycling. However, X-ray absorption fine structure measurements indicate that Ni in the surface layer is reduced and stable rock-salt structures are formed. Differential scanning calorimetry (DSC) measurements show that the heat gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…178 The formation of the rock-salt layer on the surface of NCM811 is reported to enhance the thermal stability of an NCM cathode with high Ni contents. 179 The change in the total heat generation with degradation suggests a strong correlation between the heat generation and crystal structure changes during cycling, as indicated by differential scanning calorimetry (DSC) measurements and XAS measurements. Studies focusing on the thermal stability of layered NCM materials envisaged the correlation between the thermal stability and its electrochemical performance.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…178 The formation of the rock-salt layer on the surface of NCM811 is reported to enhance the thermal stability of an NCM cathode with high Ni contents. 179 The change in the total heat generation with degradation suggests a strong correlation between the heat generation and crystal structure changes during cycling, as indicated by differential scanning calorimetry (DSC) measurements and XAS measurements. Studies focusing on the thermal stability of layered NCM materials envisaged the correlation between the thermal stability and its electrochemical performance.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…7 To improve battery specific energy and power density of highvoltage LIBs, nickel-rich layered transition metal (TM) oxide cathode materials have been the top priority both in academic research and commercial exploitation, such as Li-Ni 1−x−y Co x Mn y O 2 (NCM) and LiNi 1−x−y Co x Al y O 2 (NCA). 8,9 It has been confirmed that increasing the nickel content in the cathode can help increase battery capacity. 10 However, higher nickel content in the cathode would lead to a decrease in cycle life and thermal stability as a result of Ni 2+ and Ni 3+ ion dissolution accelerated by the nonstoichiometric Li 1−x Ni 1+x O 2 crystal structure in the electrolyte during the charging process.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) have been extensively used in our daily life due to their high energy density and long life. Despite the great success of industrialization, the booming power demands of energy storage capability in consumer markets still urgently push forward the progress of battery energy density and durability, especially in particular application fields. , The energy storage performance of LIBs depends on the collaborative property of key components including cathode, anode, electrolyte, and separator . To improve battery specific energy and power density of high-voltage LIBs, nickel-rich layered transition metal (TM) oxide cathode materials have been the top priority both in academic research and commercial exploitation, such as LiNi 1– x – y Co x Mn y O 2 (NCM) and LiNi 1– x – y Co x Al y O 2 (NCA). , It has been confirmed that increasing the nickel content in the cathode can help increase battery capacity . However, higher nickel content in the cathode would lead to a decrease in cycle life and thermal stability as a result of Ni 2+ and Ni 3+ ion dissolution accelerated by the nonstoichiometric Li 1– x Ni 1+ x O 2 crystal structure in the electrolyte during the charging process.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical crosstalk between the oxidative gas and the electrolytes/reductive anode (especially Li-metal anode), generates tremendous heat and eventually leads to the thermal safety risks of working batteries. [13][14][15] (4) Internal short circuit is another major heat resource of batteries during thermal safety risks. [16,17] Both the cathode and anode directly contact each other due to the failure of separator, leading to the enormous and uncontrolled short-circuit current and the massive joule heat.…”
Section: Introductionmentioning
confidence: 99%